2020
DOI: 10.1016/s0735-1097(20)32857-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism With Clot in Transit: An Analysis of Risk Factors and Outcomes

Abstract: me to develop the critical thinking skills and vision necessary to be successful in academia and clinically. His mentorship and direction have been invaluable, and I will carry these experiences with me throughout my career.I would also like to thank Dr. Hui Zheng for his assistance with statistical analysis.He truly helped this project come to fruition, and I sincerely appreciate all of his hard work.Additionally, I would like to thank the members of the Center for Vascular Emergencies at Massachusetts Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(67 reference statements)
2
5
1
Order By: Relevance
“…The mean age of our patients was 51.92 ± 14.74, the relatively younger age of our patients confirmed when compared with the RIETE [5] registry which is a multicenter registry that was conducted on 23,858 patients in which the mean age was 67.3 ±17.0. Also the mean age of our patients was less than that in the study made by Garvey S et al [6], that was conducted on 1121 patients in which the mean age was 60.1 ± 16.7, also in the study made by Jiménez D et al, [7] that was conducted on 2096 patients the mean age was 68.7±16.6.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The mean age of our patients was 51.92 ± 14.74, the relatively younger age of our patients confirmed when compared with the RIETE [5] registry which is a multicenter registry that was conducted on 23,858 patients in which the mean age was 67.3 ±17.0. Also the mean age of our patients was less than that in the study made by Garvey S et al [6], that was conducted on 1121 patients in which the mean age was 60.1 ± 16.7, also in the study made by Jiménez D et al, [7] that was conducted on 2096 patients the mean age was 68.7±16.6.…”
Section: Discussioncontrasting
confidence: 61%
“…In contrast the percentage of males was higher in the study made by Garvey S et al [6] 52% males and 48% females.…”
Section: Discussionmentioning
confidence: 59%
“…If CTPA demonstrates right ventricular dilatation, echocardiography may be indicated. Echocardiography is also better suited to evaluate clot in transit, another high‐risk imaging feature 55–58 . High‐risk laboratory values include an elevated troponin 59,60 .…”
Section: Methodsmentioning
confidence: 99%
“…However, this may be an overestimate due to selection bias, as an almost equal number of patients with less severe PE did not undergo echocardiography in the same cohort. 101 RHT can originate from the lower extremities, known as "thrombus in transit," 102 or can form in situ in the right atrium in patients with comorbid atrial fibrillation. 103 History of heart failure, preexisting central venous catheter, and hypotension were all associated with increased incidence of clot in transit.…”
Section: Right Heart Thrombimentioning
confidence: 99%
“…103 History of heart failure, preexisting central venous catheter, and hypotension were all associated with increased incidence of clot in transit. 102 It is estimated that thrombus in situ complicates 2% of inpatients hospitalized with PH and atrial fibrillation. 103 A meta-analysis showed that RHT is associated with increased all-cause and PE-related mortality.…”
Section: Right Heart Thrombimentioning
confidence: 99%